Energy related activities recognition using smartphones - Ngi, Wei Ping (Nanyang Technological University, 2023)
The purpose of this research is to study the existence of cars, motorcycles, and bicycles by using their distinct audio features. Several types of audio feature properties, as well as neural networks, will be discussed. Convolution Neural Network (CNN) and Feed Forward Neural Networks (FFNN) are the two neural networks used to generate high-level input about the presence of energy equipment. Neural networks are well-known for detecting single events, this project will also be modified to detect mixed events.